DEVELOPMENT OF A NEW ROTARY FEEDER DESIGN AND BASED FLOW PARAMETERS FOR A SEED FEEDER DEVICE - Aliyev, Elmurod; Mamahonov , A’zam (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract: In the article, the design of the fuzzy seed feeder device is developed. The flow characteristics are determined according to the geometric parameters of the proposed rotary feeder hopper. Graphs showing the interdependence of the numerical values of the obtained parameters were obtained.